1997
DOI: 10.1046/j.1365-2648.1997.1997026059.x
|View full text |Cite
|
Sign up to set email alerts
|

Information needs of women during early treatment for breast cancer

Abstract: This study assessed the information needs of 70 women with breast cancer being treated by surgery, chemotherapy or radiation therapy. Information needs were measured by the breast cancer version of the Toronto Informational Needs Questionnaire (TINQ-BC). All women had high information needs, irrespective of type of treatment received. They mainly wanted information about their disease, treatments and investigative tests. An examination of individual items on the TINQ-BC revealed that all women wanted informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
107
0
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(118 citation statements)
references
References 20 publications
7
107
0
4
Order By: Relevance
“…It is widely accepted that most women with invasive breast cancer require adequate information to help them accept and adjust to the diagnosis (Graydon et al, 1997) and this can enhance psychological well-being (Okamura et al, 2003). This study suggests that DCIS patients have similar needs, requiring accurate and sufficient information to facilitate adjustment, but importantly in the case of DCIS, information is needed particularly to achieve an understanding of an unfamiliar and complex condition.…”
Section: Discussion and Implications For Nursingmentioning
confidence: 85%
“…It is widely accepted that most women with invasive breast cancer require adequate information to help them accept and adjust to the diagnosis (Graydon et al, 1997) and this can enhance psychological well-being (Okamura et al, 2003). This study suggests that DCIS patients have similar needs, requiring accurate and sufficient information to facilitate adjustment, but importantly in the case of DCIS, information is needed particularly to achieve an understanding of an unfamiliar and complex condition.…”
Section: Discussion and Implications For Nursingmentioning
confidence: 85%
“…The 'Expected benefits from routine followup' and 'Needs and preferences in routine follow-up' were measured with a self-developed questionnaire, because existing questionnaires (Degner et al, 1997;Graydon et al, 1997;Mesters et al, 2001) were unsuitable for measuring specific needs and benefits in breast cancer routine follow-up. In a pilot study, the feasibility of the questionnaire was tested, for acceptability and understanding, among 15 women who were in follow-up at our breast clinic and who were treated for invasive breast cancer before January 1998.…”
Section: Measurementsmentioning
confidence: 99%
“…There is growing evidence in the literature of the effectiveness of nurse-given patient education on increase in knowledge acquisition and promotion of self-care behaviours (Derdiarian, 1989;Dodd, 1981Dodd, , 1982aDodd, , 1982bDodd, , 1983Dodd, , 1984aDodd, , 1984bDodd, , 1984cDodd, , 1987Dodd, , 1988aDodd, , 1988bDodd et al, 1996;Graydon et al, 1997;Luker et al, 1995;Nettles-Carlson, Field, Friedman & Smith, 1988;Thomas & Dodd, 1992;Weintraub & Hagopian, 1990). Also, the need to study the cost-effectiveness of nursing care has been identified by a number of authors (Henry et al, 1987;Hermansdorfer, Henry, Moody & Smyth, 1990;Ingersoll, Hoffart & Schultz, 1990).…”
Section: Literature Reviewmentioning
confidence: 99%